Primary Ciliary Dyskinesia: Longitudinal Study of Lung Disease by Ultrastructure Defect and Genotype. - Davis, Stephanie D; Rosenfeld, Margaret; Lee, Hye-Seung; Ferkol, Thomas W; Sagel, Scott D; Dell, Sharon D; Milla, Carlos; Pittman, Jessica E; Shapiro, Adam J; Sullivan, Kelli M; Nykamp, Keith R; Krischer, Jeffrey P; et al. (Am J Respir Crit Care Med, 2019)
RATIONALE: In primary ciliary dyskinesia, factors leading to disease heterogeneity are poorly understood. OBJECTIVES: To describe early lung disease progression in primary ciliary dyskinesia and identify associations between ultrastructural defects and genotypes with clinical phenotype. METHODS: This was a prospective, longitudinal (5 yr), multicenter, observational study. Inclusion criteria were less than 19 years at enrollment and greater than or equal to two annual study visits. Linear mixed effects models including random slope and random intercept were used to evaluate longitudinal associations between the ciliary defect group (or genotype group) and clinical features (percent predicted FEV and weight and height z-scores). MEASUREMENTS AND MAIN RESULTS: A total of 137 participants completed 732 visits. The group with absent inner dynein arm, central apparatus defects, and microtubular disorganization (IDA/CA/MTD) (n = 41) were significantly younger at diagnosis and in mixed effects models had significantly lower percent predicted FEV and weight and height z-scores than the isolated outer dynein arm defect (n = 55) group. Participants with CCDC39 or CCDC40 mutations (n = 34) had lower percent predicted FEV and weight and height z-scores than those with DNAH5 mutations (n = 36). For the entire cohort, percent predicted FEV decline was heterogeneous with a mean (SE) decline of 0.57 (0.25) percent predicted/yr. Rate of decline was different from zero only in the IDA/MTD/CA group (mean [SE], -1.11 [0.48] percent predicted/yr; P = 0.02). CONCLUSIONS: Participants with IDA/MTD/CA defects, which included individuals with CCDC39 or CCDC40 mutations, had worse lung function and growth indices compared with those with outer dynein arm defects and DNAH5 mutations, respectively. The only group with a significant lung function decline over time were participants with IDA/MTD/CA defects.
Keywords: Child; Cilia; Cohort Studies; Female; Genotype; Humans; Kartagener Syndrome; Longitudinal Studies; Lung; Male; Mutation; Phenotype; Prospective Studies; Respiratory Function Tests

Laterality defects other than situs inversus totalis in primary ciliary dyskinesia: insights into situs ambiguus and heterotaxy. - Shapiro, Adam J; Davis, Stephanie D; Ferkol, Thomas; Dell, Sharon D; Rosenfeld, Margaret; Olivier, Kenneth N; Sagel, Scott D; Milla, Carlos; Zariwala, Maimoona A; Wolf, Whitney; Carson, Johnny L; Hazucha, Milan J; et al. (Chest, 2014)
BACKGROUND: Motile cilia dysfunction causes primary ciliary dyskinesia (PCD), situs inversus totalis (SI), and a spectrum of laterality defects, yet the prevalence of laterality defects other than SI in PCD has not been prospectively studied. METHODS: In this prospective study, participants with suspected PCD were referred to our multisite consortium. We measured nasal nitric oxide (nNO) level, examined cilia with electron microscopy, and analyzed PCD-causing gene mutations. Situs was classified as (1) situs solitus (SS), (2) SI, or (3) situs ambiguus (SA), including heterotaxy. Participants with hallmark electron microscopic defects, biallelic gene mutations, or both were considered to have classic PCD. RESULTS: Of 767 participants (median age, 8.1 years, range, 0.1-58 years), classic PCD was defined in 305, including 143 (46.9%), 125 (41.0%), and 37 (12.1%) with SS, SI, and SA, respectively. A spectrum of laterality defects was identified with classic PCD, including 2.6% and 2.3% with SA plus complex or simple cardiac defects, respectively; 4.6% with SA but no cardiac defect; and 2.6% with an isolated possible laterality defect. Participants with SA and classic PCD had a higher prevalence of PCD-associated respiratory symptoms vs SA control participants (year-round wet cough, P < .001; year-round nasal congestion, P = .015; neonatal respiratory distress, P = .009; digital clubbing, P = .021) and lower nNO levels (median, 12 nL/min vs 252 nL/min; P < .001). CONCLUSIONS: At least 12.1% of patients with classic PCD have SA and laterality defects ranging from classic heterotaxy to subtle laterality defects. Specific clinical features of PCD and low nNO levels help to identify PCD in patients with laterality defects. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT00323167; URL: www.clinicaltrials.gov.
Keywords: Adolescent; Adult; Biopsy; Child; Child, Preschool; Cilia; DNA; DNA Mutational Analysis; Female; Humans; Infant; Infant, Newborn; Kartagener Syndrome; Male; Microscopy, Electron, Transmission; Middle Aged; Mutation; Prevalence; Prospective Studies; Tomography, X-Ray Computed; United States; Young Adult

Mutations in RSPH1 cause primary ciliary dyskinesia with a unique clinical and ciliary phenotype. - Knowles, Michael R; Ostrowski, Lawrence E; Leigh, Margaret W; Sears, Patrick R; Davis, Stephanie D; Wolf, Whitney E; Hazucha, Milan J; Carson, Johnny L; Olivier, Kenneth N; Sagel, Scott D; Rosenfeld, Margaret; Ferkol, Thomas W; et al. (Am J Respir Crit Care Med, 2014)
RATIONALE: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder of motile cilia, but the genetic cause is not defined for all patients with PCD. OBJECTIVES: To identify disease-causing mutations in novel genes, we performed exome sequencing, follow-up characterization, mutation scanning, and genotype-phenotype studies in patients with PCD. METHODS: Whole-exome sequencing was performed using NimbleGen capture and Illumina HiSeq sequencing. Sanger-based sequencing was used for mutation scanning, validation, and segregation analysis. MEASUREMENTS AND MAIN RESULTS: We performed exome sequencing on an affected sib-pair with normal ultrastructure in more than 85% of cilia. A homozygous splice-site mutation was detected in RSPH1 in both siblings; parents were carriers. Screening RSPH1 in 413 unrelated probands, including 325 with PCD and 88 with idiopathic bronchiectasis, revealed biallelic loss-of-function mutations in nine additional probands. Five affected siblings of probands in RSPH1 families harbored the familial mutations. The 16 individuals with RSPH1 mutations had some features of PCD; however, nasal nitric oxide levels were higher than in patients with PCD with other gene mutations (98.3 vs. 20.7 nl/min; P < 0.0003). Additionally, individuals with RSPH1 mutations had a lower prevalence (8 of 16) of neonatal respiratory distress, and later onset of daily wet cough than typical for PCD, and better lung function (FEV1), compared with 75 age- and sex-matched PCD cases (73.0 vs. 61.8, FEV1 % predicted; P = 0.043). Cilia from individuals with RSPH1 mutations had normal beat frequency (6.1 ± Hz at 25°C), but an abnormal, circular beat pattern. CONCLUSIONS: The milder clinical disease and higher nasal nitric oxide in individuals with biallelic mutations in RSPH1 provides evidence of a unique genotype-phenotype relationship in PCD, and suggests that mutations in RSPH1 may be associated with residual ciliary function.
Keywords: Adolescent; Adult; Child; Cilia; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genetic Association Studies; Genetic Markers; Genetic Testing; Homozygote; Humans; Kartagener Syndrome; Linear Models; Male; Middle Aged; Mutation; Nasal Mucosa; Sequence Analysis, DNA; Young Adult